Implementación de una fábrica, comercializadora y distribuidora de una línea contemporánea de muebles - Miranda, A. (2011)
The following thesis seeks to develop a familiar idea to expand the possibilities of implementation, based on the returns that could reach the idea to create this distributor of contemporary furniture manufactured at El Triunfo, being a great opportunity in this market, which now is unknown nearest provider that can meet this demand, identified by providing a modern line of furniture at low prices, using an economy of scale in production, without neglecting the quality of them. The main objective is the geographical expansion in distribution to various cities adjacent to El Triunfo. Recognizing that this project is based on the use of a raw material, such as wood, is disclosed then the contribution given to the ecological reserve of the country, with plantings and changing our production, the products shall have combinations of metal, glass and special fabric, giving a different style and each product. According to the financial study conducted has shown that the furniture factory is viable and profitable as it yields a NPV of $ $ 55,504.00 U.S., while the IRR is 113%, with these very favorable results, with which it could be given a acceptance to the idea of implementing a furniture factory at El Triunfo.